La representación del pasado sexual de Guayaquil: historizando los enchaquirados1 - Benavides, Hugo (2006)
The article assesses the role played by the enchaquirados in the historical reconstruction of Guayaquil's sexual past. In this re g a rd, the alternative reading of this pre- Hispanic homosexual harem of boys questions the city's traditionally heterosexist history; howe ve r, rather than simply blaming official historiography and pretending to offer some new historical truth, the present contribution looks to interrogate the inherent problematics of historical hermeneutics. Thought this critical evaluation of the enchaquirado's legacy, I offer some needed insight into the nature of historical production in Ecuador and in the pervasive limitations of all historical production in post-colonial contexts, particularly Latin American ones. In this manner, the article looks to place the production of Guayaquil's past (and its reigning masculinity discourse) in an eve r - changing discourse in which elements of colonial relationships, race, and regional geography play a vitally determining factor, and are constantly re-determined themselves in the process.